Creative industries: concept, features, and problems of legislative interpretation - Shtefan, Anna (Problems of legality, 2024)
The article explores the concept of creative industries, suggests their features, and analyses the list of creative industries of Ukraine in terms of correctness of legislative interpretations and substantive compliance with creative fields of activity. The definition of creative industries has been improved: these are areas of economic activity that create (produce) goods and/or provide services based on the use of intellectual (creative) capital and commercialize them by combining creative results with business solutions, which leads to the creation of added value and jobs. The use of the National Classifier of Ukraine DK 009:2010 "Classification of Types of Economic Activity" as the basis for the list of creative industries in 2019 was a wrong decision which, however, logically follows from the definition of creative industries introduced in 2018 in the Law of Ukraine "On Culture" which qualifies them as types, not spheres of economic activity. The literal application of this concept has led to the fact that the national list of creative industries has the following shortcomings: 1) artificial segmentation of one field of activity into several creative industries; 2) artificial unification of different areas of creative activity into one creative industry; 3) absence in the list of fields of activity which are essentially creative industries; 4) coverage by the list of fields of activity which do not produce creative products and do not provide creative services. It is concluded that a new, qualitatively different list of creative industries needs to be approved.